1150 Obstructive Sleep Apnea-dependent Racial/ethnic And Sex-specific Mechanisms Underlying Alzheimer's Disease Risk: A Retrospective Cohort Analysis Of In-lab PSG Sleep Study Data. (27th May 2020) - Bubu, O M; Turner, A D; Parekh, A; Mullins, A; Kam, K; Umasabor-Bubu, O Q; Mbah, A K; Williams, N J; Varga, A W; Rapoport, D M; Ayappa, I; Jean-Louis, G; et al.
Abstract: Introduction: We examined race and sex-specific biologic mechanisms of the relationship between obstructive sleep apnea (OSA) and incident AD. Methods: Retrospective cohort analysis utilizing in-lab PSG sleep study data conducted among older adults between 2001 and 2005. OSA was defined using AHI4%. Participants had no history of cognitive decline or AD at baseline and included 663 (284 Non-Hispanic White (NHW), 207 Black/African-American (AA) and 172 Hispanic) OSA-patients matched on age, sex, race, BMI, 1:1 ratio to 663 (unexposed cohort I from sleep clinic) and 1:4 ratio to 2652 (unexposed cohort II from non-sleep clinics) non-OSA individuals. Incident AD was assessed annually from 2001-2013 with ICD-9-CM code 331.0. Adjusted cox proportional hazard regression models examined race and sex-specific biologic mechanisms including hypoxia, fragmentation and duration measures of OSA and AD risk. Results: Of the 3, 978 participants, 2, 148 (54%) were women. Mean age at baseline was 72.6 (7.3) years. Over a mean follow-up time of 8.6 (1.4) years, 358 (9%) individuals (212 female) developed AD (119 NHW, 134 AAs, and 105 Hispanics). Relative to non-OSA individuals, OSA-patients had a higher risk of incident AD, with AAs and females showing stronger risk estimates (aHR: 2.24, 1.83, and 1.73, P <.001 for all, for AAs, Hispanics and NHW respectively; and aHR: 2.38, and 1.37, P <.001 for all, for female and male respectively). Measures of hypoxia, sleep fragmentation and sleep duration were associated with increase AD risk ( P <.01 for all). Relative to NHW, AAs and Hispanics demonstrated up to 20% stronger effects/estimates on hypoxia and sleep duration measures. Relative to males, females demonstrated up to 25% stronger effects/estimates on sleep fragmentation measures, and 15% weaker effects/estimates on hypoxia measures ( P <.01 for all). Conclusion: Among OSA-patients, mechanisms related to hypoxia, sleep fragmentation and duration measures increase AD risk and may underlie race/ethnicity and sex disparities in AD. Support: NIH/NIA/NHLBI (L30-AG064670, CIRAD P30AG059303 Pilot, T32HL129953, R01HL118624, R21AG049348, R21AG055002, R01AG056031, R01AG022374, R21AG059179, R01AG056682, R01AG056531, K07AG05268503, K23HL125939)